Assessment of physical activity among pregnant women in context of weight gain in pregnancy - Mączka, Martyna; Sass, Anna; Wojtyla, Anna (Journal of Education, Health and Sport, 2017)
INTRODUCTION Repeatedly during and with the follow up pregnancy, there is a noticeable phenomenon of decreasing tolerance of physical activity. This condition is caused by the restriction or total abandonment of physical activity. Reducing or insufficient exercising physical activity in connection with an inappropriate diet leads to excessive body weight gain and a number of complications. RESEARCH OBJECTIVE The main object of the study is to evaluate the physical activity among pregnant women. Furthermore is to differentiate the somatic features of pregnant women due to their physical activity. MATERIALS AND METHODS In study observation take a part the 353 pregnant women, the participants of natal school, in 26 weeks of gestation (hbd). All primagravidas were in physiological pregnancy. Physical activity was assessed by using a pedometer (Yamax SW700), device was fixed on the spina iliaca anterior superior, prior personalization of data (based on the length of the step, body weight and height). Women were aware of using pedometers, the data was daily recorded for 7 days. In addition, 156 women participated in stimulated physical activity (Pilates gymnastic) of their own free will. CONCLUSIONS The walking as a form of physical activity has positively affects on the weight gain of pregnant women. Daily recommended physical activity such walking, differentiates body weight gain during pregnancy. In contrast, stimulated physical activity by Pilates gymnastics do not show differences in body weight gain during pregnancy. Optimal physical activity from walking is associated with lower body weight gains compared to stimulated physical activity of Pilates, which is not associated with weight gain. The more a women walk, the less weight gain they have.